2008
DOI: 10.1111/j.1365-2710.2008.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C level for better assessment of glomerular filtration rate in cystic fibrosis patients treated by amikacin

Abstract: We showed that the rate of U-NAG/U-creatinine is a suitable marker for monitoring tubular nephrotoxicity in CF patients. Serum creatinine and estimated creatinine clearance are modest predictors of GFR in CF patients. CyC appears to be a better marker of GFR than serum creatinine concentration or creatinine clearance in our study. Serum CyC levels and CyC clearance showed greater ability to predict amikacin clearance during therapy than creatinine clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…This was in agreement with previous findings, showing that CysC was more precise to predict GFR than the creatinine‐based Cockcroft–Gault equation in elderly patients . Only one study was conducted in children, showing that amikacin clearance was better correlated with CysC than serum creatinine . In addition, Neamatollah et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was in agreement with previous findings, showing that CysC was more precise to predict GFR than the creatinine‐based Cockcroft–Gault equation in elderly patients . Only one study was conducted in children, showing that amikacin clearance was better correlated with CysC than serum creatinine . In addition, Neamatollah et al .…”
Section: Discussionsupporting
confidence: 92%
“…The underlying disease and mechanisms of renal impairment were variable in the present analysis, as the studies were conducted in healthy volunteers, cystic fibrosis and cancer patients. In patients with cystic fibrosis, amikacin clearance was better correlated with CysC than creatinine . These results are in accordance with the findings by Beringer et al who reported that the CysC formula demonstrated greater sensitivity and specificity to quantify GFR in cystic fibrosis patients compared with the equations with serum creatinine (Cockcroft–Gault; MDRD).…”
Section: Discussionsupporting
confidence: 90%
“…UCr has similarly been found to be a problematic normalization factor both within certain populations (2, 4, 24) and when used to compare biomarker measurements across different demographic groups with known variability in UCr (24, 25). Previous studies have likewise shown decreased UCr levels from 24-hour urine samples in the stable CF population compared to age-matched control patients (2526) as well as decreased renal function with aminoglycoside use (1013, 2728). This, in addition to the association with SG observed here, suggests that the lower UCr values in the hospitalized CF population are likely the result of lower creatinine production and impaired renal function rather than lower specimen concentration.…”
Section: Discussionmentioning
confidence: 72%
“…Finally, CysC was found to better predict elimination of renally excreted drugs in adults compared to Scr or CrCL (29)(30)(31)(32). This is only the second report to identify this new biomarker as a predictor of renal drug clearance in children at the expense of Scr or CrCL (33). Treatment with vasopressors (mainly norepinephrine; 14/15 patients) was also associated with an 18% decrease in amoxicillin clearance.…”
Section: Discussionmentioning
confidence: 77%